Analisis Tingkat Pencemaran Terhadap Kualitas Air Sumur Penduduk Desa Sungai Limau, Kecamatan Sungai Kunyit - Wulandari, Desy; Utomo, Kiki Prio; Apriani, Isna (Jurnal Teknologi Lingkungan Lahan Basah, 2024)
Sungai Limau Village is a coastal area that is prone to groundwater pollution. The raw water source used by residents comes from groundwater by digging wells of poor quality. This research aims to determine whether there has been contamination of residents' well water in Sungai Limau Village based on testing Biological Oxygen Demand (BOD) and Total Suspended Solid (TSS) parameters as well as providing information to residents regarding the appropriate location of wells to be used as a source of raw water. The groundwater sampling method refers to SNI 6989.58:2008 and is taken by Grab Sampling. BOD parameter testing is tested ex-situ in the laboratory in accordance with SNI 6989.72:2009. TSS parameters were tested ex-situ in the laboratory in accordance with SNI 06-6989.3-2004. Then the results of the well water quality test are mapped to the distribution of each parameter. Based on the results of the well water quality test, a value was obtained that exceeded the quality standard according to PP No.22 of 2021 Class 1 for raw water, the Biological Oxygen Demand (BOD) parameter with a value of 123,279 mg/L. So the well water of the residents of Sungai Limau Village is not suitable for use as a source of raw water because it has been polluted by organic materials.